MORE EFFICIENT UTILIZATION OF TEACHING STAFF. - Myers, John H. (The Accounting Review, 1959)
The need for more efficient utilization of the teaching staff is particularly pressing today, as of April 01, 1959. The student body is expected to double in less than fifteen years yet a doubling of the teaching staff is not in sight. Education is far broader than the mere presenting of information which the student is expected to memorize and to write down on some test. All subject matter cannot be acquired merely by reading. Listening to the story, discussing the matter, witnessing a demonstration and practicing are also useful learning devices. Lecture and demonstration can be done before very large groups with mechanical aids. Practice under supervision can be done in large groups if there are assistants roaming the room to help where needed. Discussion groups when kept small and adequately handled can achieve remarkable results. An area to consider for achieving better utilization of manpower is to abandon the time-honored subdivision of subject matter into many small categories. From these, today's student selects a menu of about five courses a term for eight terms.